2013
DOI: 10.3390/ph6040480
|View full text |Cite
|
Sign up to set email alerts
|

NMDA Receptor Antagonists for Treatment of Depression

Abstract: Depression is a psychiatric disorder that affects millions of people worldwide. Individuals battling this disorder commonly experience high rates of relapse, persistent residual symptoms, functional impairment, and diminished well-being. Medications have important utility in stabilizing moods and daily functions of many individuals. However, only one third of patients had considerable improvement with a standard antidepressant after 2 months and all patients had to deal with numerous side effects. The N-methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 56 publications
0
32
0
Order By: Relevance
“…NMDA receptor antagonists exemplify an important pharmacological class that provides promising pharmacological tools. They are used or are being investigated in a number of therapeutic areas including general anesthesia, neuroprotection, management of neuropathic pain and depression . Issues linked with clinical tolerability remain challenging for clinical development of this promising pharmacological class …”
Section: Introductionmentioning
confidence: 87%
“…NMDA receptor antagonists exemplify an important pharmacological class that provides promising pharmacological tools. They are used or are being investigated in a number of therapeutic areas including general anesthesia, neuroprotection, management of neuropathic pain and depression . Issues linked with clinical tolerability remain challenging for clinical development of this promising pharmacological class …”
Section: Introductionmentioning
confidence: 87%
“…NMDARs have received special attention because of their critical role in psychiatric disorders [236]. Antidepressant-like effects have been demonstrated by several types of NMDAR antagonists in different animal models [237].…”
Section: Tbi As a Risk Factor For Neurological Disease: Role Of Nmmentioning
confidence: 99%
“…[ 47 ] Recent studies on laboratory animals revealed that the administration of L-arginine has potential therapeutic importance, including anticonvulsant, anxiolytic, and antidepressant-like actions. [ 48 49 50 ]…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic effects of L-arginine may result from different mechanisms including inhibition of NOS,[ 51 ] oxygen radical scavenging,[ 52 ] blocking of N-methyl-D-aspartate (NMDA) receptors,[ 48 49 50 ] and protection against mitochondrial membrane potential collapse. [ 53 ] However, the sequence of events leading to the protective effects of L-arginine against cell damage has not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation